Determinants of Antibiotics Misuse by the Parents in Children: A Survey From Northern Region of Saudi Arabia (Bangladesh Journal of Child Health, 2017)
Objectives: To investigate knowledge, beliefs and practices associated with parental antibiotic misuse.Methods: This cross sectional study was conducted among the parents visited 4 major shopping malls (selling medicines) of Tabuk, Saudi Arabia from June to December 2015. Self-prescription of antibiotics for a child in the past year was defined as antibiotic misuse was noted.Results: From 610 parents (60.5% mothers and 39.5% fathers) 11.6% reported selfprescription. Responded parents differed by age, education, number of children and profession. Parents responded that antibiotics should be used for runny nose, sore throat, cough and fever (50%); to reduce symptom severity and duration (57.7%), should be stopped on clinical improvement (28.7%), are effective in viral infections (68.6%) and if used by the other family members should be given to the children (20.1%). Determinants of misuse in a multivariable model, were income, number of kid, type of infection treated last year, knowledge of diseases requiring antibiotics, or being unsure, using same antibiotics used by the other family person, unsure of such use and adjusting for the type of responding parent. Logistic regression model shows that those who incorrectly had knowledge that any type of infection with fever needs to be treated by antibiotics had twice the odds of misusing antibiotic (AOR: 2.17, 95%CL: 1.19-3.96), Parents who believed that it was acceptable to administer the same antibiotics to their children that were used for a similar illness by any other family member in the past; had thrice the Odds of using non-prescribed antibiotics (AOR=3.01, 95% CI=1.77-5.37). Similarly, those who were not sure about the use of prior antibiotics by any other family member were also three times more likely to misuse antibiotics (AOR:3.00,95%CI/ :1.00-9.01). Parents reporting monthly income of less than SAR 5000 had twice the Odds of misusing anti biotics (OR:2.00,95% CI:1.05-3.83).Conclusion: Parents having low income, more than two kids below 12 years age, low education level, inappropriate beliefs and practices are vulnerable for misusing antibiotics in their children.Bangladesh J Child Health 2016; VOL 40 (2) :64-71